风力压缩空气储能式海水淡化系统 (2016)
本发明公开了种风力压缩空气储能式海水淡化系统，包括风力涡轮机、行星齿轮、提水泵、膜式气压淡化单元、涡旋机等。其中，风力涡轮机、提水泵及涡旋机分别经变速机构和行星齿轮行星架、齿圈及太阳轮相连，提水泵提升预处理海水，膜式气压淡化单元内有桶形反渗透膜和球形弹性气囊，球形弹性气囊经比例阀和气罐相连，配合提水泵可实现反渗透水压柔性无级控制；涡轮机回收废水压能辅助驱动提水泵；压缩空气储能由涡旋机和气罐以及两并联气路组成，多余风能驱动涡旋机压缩，风能不足时，涡旋机膨胀逆转补充提水泵差额功率。本发明采用压缩空气储能稳定海水淡化工况，结合弹性气囊的反渗透压柔性无级控制，大幅提高海水淡化效率以及渗透膜使用寿命。 The invention discloses a wind compressed air energy storage type seawater desalinization system which comprises a wind turbine, a planetary gear, a lift pump, a membrane-type air pressure desalinization unit, a vortex machine and the like, wherein the wind turbine, the lift pump and the vortex machine are respectively connected with a planetary-gear planet carrier, a gear ring and a sun gear by a shift gear; the lift pump lifts up preprocessed seawater; a barrel-shaped reverse osmosis membrane and a spherical elastic air bag are arranged in the membrane-type air pressure desalinization unit; the spherical elastic air bag is connected with an air tank by a proportional valve and is matched with the lift pump so as